THE IMPORTANCE OF STUDENTS' COLLABORATION IN THE E-LEARNING IMPLEMENTATION - Ridwan Sanjaya; Henny Putri Saking Wijaya (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
E-Learning. as in the use of technology for teaching and learning purposes. has been promoted in Indonesia to be an alternative of learning process. Although it was late if it is compared with other Asian countries. it is a step forward for a learning process in Indonesia. However. many of the E-Learning practices involve the uploading of digitized content materials to a learning management system. In the present. the activity of student is downloading the content materials from his/her lecturer only. It makes the E-Learning website have no competitive advantage compared with the common website. The E-Learning website should be a medium for the students 10 interact. discuss. and collaborate ill their project work. A collaborative learning can increase better quality of learning because there is a unity of thinking and learning skills. There are several kinds of software which provide the Learning Management Systems (LMS) but not all of them can give media for collaboration. A tutor is one of the LMS that can give a media for the students to create a draft using its virtual room. Each students can give inputs or revise the draft to improve the quality. Then. the final report can be shared to other students using the virtual library, after the draft is finished.